2017
DOI: 10.1016/j.cmet.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A PDGFRα-Mediated Switch toward CD9high Adipocyte Progenitors Controls Obesity-Induced Adipose Tissue Fibrosis

Abstract: Obesity-induced white adipose tissue (WAT) fibrosis is believed to accelerate WAT dysfunction. However, the cellular origin of WAT fibrosis remains unclear. Here, we show that adipocyte platelet-derived growth factor receptor-α-positive (PDGFRα) progenitors adopt a fibrogenic phenotype in obese mice prone to visceral WAT fibrosis. More specifically, a subset of PDGFRα cells with high CD9 expression (CD9) originates pro-fibrotic cells whereas their CD9 counterparts, committed to adipogenesis, are almost complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
284
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(323 citation statements)
references
References 52 publications
23
284
1
4
Order By: Relevance
“…Using macrophage-specific markers CD64 and MerTK, 38 the population of CD64 À CD11c + ATDCs is identifiable and distinct from CD64 + CD11c + and CD64 + CD11c À ATM pools. CD9 high adipocyte progenitors 41 have been identified as correlating with AT fibrosis in humans, and CD9 is also found on DCs 42 to control antigen presentation, suggesting a potential broader role for CD9 in AT biology that has yet to be understood. 39 Single-cell RNA sequencing and clustering analysis in murine samples suggested that three main ATM populations can be identified by the markers CD9 and Ly6C: 40 Ly6c + ; Ly6c À CD9 + ; and Ly6c À CD9 À .…”
Section: Atm Heterogeneity In Micementioning
confidence: 99%
“…Using macrophage-specific markers CD64 and MerTK, 38 the population of CD64 À CD11c + ATDCs is identifiable and distinct from CD64 + CD11c + and CD64 + CD11c À ATM pools. CD9 high adipocyte progenitors 41 have been identified as correlating with AT fibrosis in humans, and CD9 is also found on DCs 42 to control antigen presentation, suggesting a potential broader role for CD9 in AT biology that has yet to be understood. 39 Single-cell RNA sequencing and clustering analysis in murine samples suggested that three main ATM populations can be identified by the markers CD9 and Ly6C: 40 Ly6c + ; Ly6c À CD9 + ; and Ly6c À CD9 À .…”
Section: Atm Heterogeneity In Micementioning
confidence: 99%
“…Diverse beige progenitor lineages may exist; in mice, both beige adipocyte-specific progenitors and beige/white adipocyte-bipotent PDGFRα + progenitors have been reported (60, 178, 338). Notably, a subpopulation of PDGFRα + mesenchymal progenitors (PDGFRα + CD9 high ) also differentiates into fibrogenic cells in obesity, promoting adipose tissue fibrosis (201). …”
Section: Bat and Beige Fat Developmentmentioning
confidence: 99%
“…However, activation of PDGFRα signaling was also reported to stimulate differentiation of adipose mesenchymal progenitors into fibrotic cells at the expense of suppressing adipogenesis (138). Interestingly, a recently study reported an identification of PDGFRα + CD9 high and PDGFRα + CD9 low subsets in adipose tissue (201). The PDGFRα + CD9 high mesenchymal progenitors differentiate into fibrogenic cells, whereas the PDGFRα + CD9 low subset differentiate to adipocytes (201).…”
Section: Humoral Regulation Of Brown and Beige Fat Thermogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…high cells generated fibroblasts whereas CD9 low progenitors were transcriptionally committed to the adipose lineage (18). A more comprehensive understanding of mesenchymal heterogeneity in wounded and unwounded skin will allow researchers to better define the lineage relationships between dermal cells and target specific cellular subsets and signaling pathways that could selectively activate specific "fibroblast" subsets to impact dermal healing and scarring.…”
mentioning
confidence: 99%